The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12887-016-0679-6
|View full text |Cite
|
Sign up to set email alerts
|

Higher body mass index associated with severe early childhood caries

Abstract: BackgroundSevere Early Childhood Caries (S-ECC) is an aggressive form of tooth decay in preschool children affecting quality of life and nutritional status. The purpose was to determine whether there is an association between Body Mass Index (BMI) and S-ECC.MethodsChildren with S-ECC were recruited on the day of their slated dental surgery under general anesthesia. Age-matched, caries-free controls were recruited from the community. All children were participating in a larger study on nutrition and S-ECC. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
143
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(149 citation statements)
references
References 22 publications
6
143
0
Order By: Relevance
“…As previously reported 16 , this group had lower than expected IQ. Although IQ is not a proxy for learning potential, impairments of cognitive development, including those associated with very preterm birth, are expected to impede academic achievement 21,22 .…”
supporting
confidence: 85%
See 2 more Smart Citations
“…As previously reported 16 , this group had lower than expected IQ. Although IQ is not a proxy for learning potential, impairments of cognitive development, including those associated with very preterm birth, are expected to impede academic achievement 21,22 .…”
supporting
confidence: 85%
“…Neuropsychological correlates were examined using 12 of the measures included in the original follow-up test battery 16 . Five composite measures were created by averaging the standard scores across each pair of test measures to reduce the number of variables included in the analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A third showed that the technology could be employed after radiotherapy for head and neck cancer distorted the anatomy 57 . The technology was useful in the management of OSA in a patient with Down’s syndrome, where CPAP therapy adherence is very, very low 58 . Finally there is a report of normalization of AHI which illustrated that HNS could be used in Stanford model of progression in those who did not respond to Phase I and II procedures used in this center 59 .…”
Section: Clinical Management In the Post-approval Eramentioning
confidence: 99%
“…25 Another study conducted in Manitoba showed that significantly more children with S-ECC had significantly higher mean BMI z-scores than caries-free children (0.78 ± 1.26 vs. 0.22 ± 1.36, p = 0.002). 34 Also, there were many studies with no statistically significant association between dental caries and different categories of BMI i.e. either in normal, underweight, overweight and obese category.…”
Section: Discussionmentioning
confidence: 99%